NOTAS - O CAOS E A INTERDISCIPLINARIDADE - Almeida, Ernani Ribeiro de; Almeida, Fabiana Ribeiro de; Pedrochi, Franciana; Phippsen, Gisele Strieder; Sato, Francielle; Simonetti, Gustavo Max Dearo; Mantovani, Iara Frangiotti; Maeda, Iris Antônio; Silva, Kelly Christine da; Zan, Kleto Michel; Andrade, Marcelo Freitas de; Sanches, Mônica Bordim; et al. (Arquivos do Mudi, 2012)
O presente artigo busca dar uma visão geral sobre a teoria do caos e suas aplicações.